Double-closed-loop control method for virtual synchronous machine without alternating-current voltage sensor - ZHANG XING; WU MENGZE; WU YUHANG; FU XINXIN; CHEN SIYU; ZHU QIAOHUA; ZHAN XIANGDUI (2022)
The invention discloses a virtual synchronous machine double-closed-loop control method without an alternating-current voltage sensor, and belongs to the technical field of power electronics. The virtual synchronous machine comprises a direct current side voltage source, a three-phase full-bridge inverter circuit, a three-phase LC filter, a three-phase power grid impedance and a three-phase power grid. The control method comprises the step of obtaining a power grid voltage estimated value through three times of low-pass filtering. According to the control method, on the premise that the power grid angular frequency does not need to be accurate and power grid voltage background harmonics are not amplified as far as possible, the power grid voltage is estimated instead of being sampled, so that the number of alternating current sensors in the virtual synchronous machine double-closed-loop control system is reduced, the cost of a grid-connected voltage source converter is reduced, and the system reliability is i